2004
DOI: 10.1007/s10126-004-1100-2
|View full text |Cite
|
Sign up to set email alerts
|

DNA Microarray for Rapid Detection of Mitochondrial DNA Haplotypes of Chum Salmon

Abstract: For use in genetic stock identification, we developed an oligonucleotide (DNA) microarray hybridization method for rapid and accurate detection of nucleotide sequence variations in 20 previously identified variable nucleotide sites in about 500 bp within the 5' half of the control region of mitochondrial DNA of chum salmon (Oncorhynchus keta). The method includes immobilization of synthesized oligonucleotides containing respective polymorphic sites on a glass slide precoated with polycarbodiimide resin, a 2-ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…An oligonucleotide microarray that detects these SNPs was developed for rapid identification of these chum salmon haplotypes (Moriya et al, 2004). In the present study, the mtDNA haplotype of individual pre-migratory fish was identified by this technique.…”
Section: Identification Of Mitochondrial Dna Haplotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…An oligonucleotide microarray that detects these SNPs was developed for rapid identification of these chum salmon haplotypes (Moriya et al, 2004). In the present study, the mtDNA haplotype of individual pre-migratory fish was identified by this technique.…”
Section: Identification Of Mitochondrial Dna Haplotypesmentioning
confidence: 99%
“…1A). Japanese populations were identified on the basis of mitochondrial DNA (mtDNA) haplotypes that were determined with DNA microarray (Moriya et al, 2004). In autumn, homing adults were collected along their migratory pathway in the Ishikari River-Ishikari Bay system in Hokkaido, Japan.…”
Section: Introductionmentioning
confidence: 99%
“…There is indeed a consensus that regulation of gene expression is a fundamental mechanism underlying the complex processes of cell differentiation and morphogenesis during ontogenesis of an organism. Recently, microarrays have dramatically accelerated many types of investigations in marine organisms, been especially used for comparative genomic hybridization (Fish; Moriya et al, 2004 and2007) and for monitoring the expression levels of thousands of genes simultaneously in order to study the effects of certain treatments (Algae; Jamers et al, 2006), diseases (Crustaceans; Wang et al, 2006) and transgenesis manipulation (Mori et al, 2007) on transcriptome. Over the last two decades, studies based on whole-body or tissue-specific microarray approaches have investigated gene expression profiles during embryogenesis in several species (Drosophila, White et al, 1999;Xenopus, Baldessari et al, 2005;mouse, Tanaka et al, 2000) including fish (zebrafish, Ton et al, 2002;sea bream, Sarropoulou et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Preparation of the DNA microarray for the 30 mtDNA haplotypes was described previously [8,9]. In brief, each synthesized 17-to 20-mer oligomer contained the previously identified single-nucleotide mutation or no mutation [5,6] in the middle of the sequence.…”
Section: Haplotype Detection By Dna Microarraymentioning
confidence: 99%
“…Recently, we developed a DNA microarray for rapid and accurate identification of all the single-nucleotide polymorphisms (SNPs) occurring in the 20 variable sites of the 5 0 half of chum salmon mtDNA control region [8], which defines all 30 mtDNA haplotypes of three clades (A, B, and C) as described previously [6]. Noticeable features of this method include immobilization of oligomers containing the SNP sites with an appropriate length on a resin-precoated glass slide, quick hybridization with labeled target fragments amplified by polymerase chain reaction (PCR), and optical signal detection by conventional histochemical coloring method without an expensive fluorescence image detector.…”
Section: Introductionmentioning
confidence: 99%